The Covenants of the Patriarchs with Foreigners at Beersheba - Dziadosz, Dariusz (The Biblical Annals, 2023)
The author of this paper seeks the original historical context as well as the oldest form, structure and concept of the biblical records of the covenants of Abraham and Isaac with the local ruler(s) as recorded in Gen 21:22–24, 25–33; 26:26–31. The patriarchs, who enjoy the status of foreign/sojourner/ resident in the land of the Philistine king, Abimelek, and their peaceful agreements are depicted in three biblical sources, which are very similar to each other in terms of structure and literary context. Those are compared with selected Hittite, Babylonian and Assyrian records of the royal covenants from the 2 millennium BC. The methodology adopted in the research allowed several important formal and substantive points of contact to be noted in the compared sources. Through this comparison, the paper confirms that Gen 21:22–24, 25 33; 26:26–31 reflects two ancient patterns of bilateral covenants between the monarch and an equal or subordinate social partner: royal grants and suzerain-vassal treaties. The paper also discusses the socio-cultural and legal spectrum of the Near Eastern royal procedures and how they were re-edited and adapted by the editors responsible for the current version of the biblical cycles about the patriarchs.